2003
DOI: 10.1083/jcb.200305112
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the Notch and TGF-β signaling pathways mediated by interaction of the Notch intracellular domain with Smad3

Abstract: The Notch and transforming growth factor-β (TGF-β) signaling pathways play critical roles in the control of cell fate during metazoan development. However, mechanisms of cross-talk and signal integration between the two systems are unknown. Here, we demonstrate a functional synergism between Notch and TGF-β signaling in the regulation of Hes-1, a direct target of the Notch pathway. Activation of TGF-β signaling up-regulated Hes-1 expression in vitro and in vivo. This effect was abrogated in myogenic cells by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
262
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(299 citation statements)
references
References 25 publications
21
262
1
2
Order By: Relevance
“…Although the conclusion above is the most likely, the data at hand could still support the notion that TGF-␤ signaling is enhancing Notch-mediated effector function, rather than the other way around. This arises from that fact that while in these studies we showed that Notch signaling enhances TGF-␤ function, in other studies cited above the enhancement was mutual (28). This latter possibility would be supported by evidence that Notch signaling has an inherently negative effect on T cell and/or APC function; however, this does not seem to be the case.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Although the conclusion above is the most likely, the data at hand could still support the notion that TGF-␤ signaling is enhancing Notch-mediated effector function, rather than the other way around. This arises from that fact that while in these studies we showed that Notch signaling enhances TGF-␤ function, in other studies cited above the enhancement was mutual (28). This latter possibility would be supported by evidence that Notch signaling has an inherently negative effect on T cell and/or APC function; however, this does not seem to be the case.…”
Section: Discussioncontrasting
confidence: 42%
“…Upon binding with its ligands (Jagged1 and 2 and Delta-like1, 3, and 4), it releases its intracellular domain into the cytoplasm which then translocates to the nucleus (19). Recently, it has been shown that the released signaling models arising from Notch1 activation enhance Smad signaling function in fibroblast and other mesenchymal cells (28), suggesting that Notch1 signaling could interact with the TGF-␤ signaling occurring in Treg function.…”
mentioning
confidence: 99%
“…Moreover, previous results have shown an interaction between Notch and TGF-β pathways [8][9][10]. We surmise that Notch1 affects effector T-cell responses in the presence of Treg cells through a TGF-β signaling mechanism.…”
Section: Notch Suppresses the Proliferation Of Cd4 + Cd25 − T Cells Tsupporting
confidence: 60%
“…It is well established that Hes1 expression can be regulated by Notch/Rbpjκ-independent signaling before E8.5 (Hatakeyama et al, 2004;Kageyama et al, 2005). Additionally, Rbpjκ-independent expression of Notch factors, including Hes genes, can be mediated by members of the BMP (Dahlqvist et al, 2003;Itoh et al, 2004) Kadesch, 2001), WNT/β-catenin (Axelrod et al, 1996;Hayward et al, 2005) and Shh (Wall et al, 2009) pathways throughout embryonic development. However, only a few studies have shown that Hes5 can be modulated by Notch/Rbpjκ-independent signaling occurring at two distinct time points: before E8.5 (Donoviel et al, 1999;Hitoshi et al, 2011) and during adult neurogenesis (Matsuda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%